Edukasi Tentang Gizi Seimbang Bagi Remaja Dalam Upaya Peningkatan Pengetahuan Mengenai Kebutuhan Gizi Di Wilayah Kerja Puskesmas Somba Opu - Nurjannah Supardi; Julia Fitrianingsih (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
In human life, adolescence is a very important period. During this period, the initial process of maturation of the reproductive organs occurs. In this phase, adolescents will experience physical growth accompanied by mental, cognitive and psychological development. Lack of adequate nutrition during this period can cause disruption and obstacles in adolescent growth. One program that can be carried out to achieve and maintain normal nutritional status in adolescents is by implementing a balanced nutritional intake. This community service activity is carried out using nutrition education methods for teenagers. Through this service activity, it is hoped that there will be an increase in knowledge among teenagers regarding the importance of implementing a balanced nutritional intake for teenagers, which in turn is hoped that teenagers will be able to achieve and maintain normal nutritional status. This activity was attended by 23 teenagers in the working area of ​​the Somba Opu Health Center, Gowa Regency. The knowledge score results show that before being given counseling about balanced nutrition, the average knowledge score for teenagers was in the medium category, namely 60,8%. After following the counseling regarding balanced nutrition and carrying out a posttest, the results showed that the teenagers' knowledge scores increased to an average of 65,22% in the high category. This shows that there is an increase in knowledge among teenagers regarding balanced nutrition after attending this counseling.